Alterations in Placental Gene Expression of Pregnant Women with Chronic Chagas Disease - Juiz, Natalia Anahí (2018)
Trypanosoma cruzi infection in women of reproductive age is associated with congenital transmission and adverse pregnancy outcomes. The placenta is a key barrier to infection. Gene expression profiles of term placental environment from T. cruzi–seropositive (SP) and -seronegative (SN) mothers were characterized by RNA-Seq. Nine pools of placental RNA paired samples were used: three from SN and six from SP tissues. Each pool consisted of female/male newborns and vaginal/cesarean delivery binomials. No newborn was congenitally infected. T. cruzi satellite DNA quantitative PCR in placental tissues and maternal and neonatal blood, and parasite 18S quantitative RT-PCR from placental RNA were negative, except in three SP women's bloodstream. To identify pathways associated with maternal T. cruzi infection, a gene-set association analysis was implemented: SP placental samples showed overexpression of inflammatory response and lymphocytic activation, whereas numerous biosynthetic processes were down-regulated. About 42 genes showed a significant fold-change between SP and SN groups. KISS1 and CGB5 were down-regulated, whereas KIF12, HLA-G, PRG2, TAC3, FN1, and ATXN3L were up-regulated. Several expressed genes in SP placentas encode proteins associated with preeclampsia and miscarriage. This first transcriptomics study in human term placental environment shows a placental response that may affect the fetus while protecting it from parasite infection; this host response could be responsible for the low rate of congenital transmission in chronic Chagas disease.